2000
DOI: 10.1063/1.125953
|View full text |Cite
|
Sign up to set email alerts
|

Short-range order in ultrathin film titanium dioxide studied by Raman spectroscopy

Abstract: It is demonstrated here that nonresonant Raman spectroscopy can be used for unequivocal determination of short-range order in ultrathin films, using different structures of titanium dioxide as the model system. Titania films as thin as 7 nm sputter deposited on 〈111〉 Si have been analyzed and their phase content determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 23 publications
3
48
0
Order By: Relevance
“…5. These spectra have the similar characteristics with the five Raman peaks around 155, 202, 399, 511, and 624 cm À1 , corresponding to the Raman active fundamental modes for anatase phase [49,50]. No other phases like rutile or TiN were detected.…”
Section: Article In Pressmentioning
confidence: 53%
“…5. These spectra have the similar characteristics with the five Raman peaks around 155, 202, 399, 511, and 624 cm À1 , corresponding to the Raman active fundamental modes for anatase phase [49,50]. No other phases like rutile or TiN were detected.…”
Section: Article In Pressmentioning
confidence: 53%
“…That the a grains under go faster dissolution can be seen from the Raman spectra from the a grains where fewer Raman features are found in Fig. 3A in the range expected for titanium oxides [23][24][25][26][27][28]. The broadness of the Raman peaks in Fig.…”
Section: Discussionmentioning
confidence: 93%
“…As the temperature increases above 500 Figure 5 depicts the Raman spectrum between 300 and 800 cm -1 . Taken at a 500 o C and 550 °C, the peaks at 447.9 and 612 cm -1 [13] correspond to the rutile phase of TiO 2 . It should be observed that at higher temperatures new peaks can be originated.…”
Section: Methodsmentioning
confidence: 94%